Theological Teachings of The Qadiani Ahmadiyya and The Jehovah’s Witnesses: A Comparative Study - Fitriani, Fitriani; Arifinsyah, Arifinsyah (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2021)
Plurality in Indonesia has been dealt with a variety of religious sects that hold ‘controversial’ concepts of aqidah (religious creeds). Example includes the Qadiani Ahmadiyya and the Jehovah's Witnesses. This paper aims to study the core of religious teachings of the two sects, and how they are different from the mainstream. This work is a qualitative research with a comparative method, used to explore the diversity of religious understandings of the sects under study. This work found that both sects share some similarities as well as differences. concludes that there are similarities and differences between the two. The Qadiani Ahmadiyya denies Muhammad as the last messenger and believes that Mirza Ghulam Ahmad who is a prophet, and has received God’s revelation. Meanwhile, the Jehovah's Witnesses rejects the doctrine of Trinity and hellfire, believing that mankind will live eternally and God almighty will not torment people forever in hell. It can be concluded that these understandings are considered unique and often seen as deviating from the mainstream teachings.